RESILIENSI DAN KEBAHAGIAAN PADA CAREGIVER ODGJ - Marannu, Gitareja Maega; Huwae, Arthur (Psikologi Prima, 2023)
In various professions, work is often faced with pressure and risk from every task and responsibility undertaken. The same thing also happened to ODGJ caregivers when carrying out their duties. It becomes a challenge for caregivers to provide optimal services and assistance to ODGJ, which must be interpreted joyfully. Regardless of the role, as a caregiver, you must form good self-resilience to carry out your duties. Therefore, this study aims to determine the relationship between resilience and happiness in ODGJ caregivers. The method used is a quantitative correlation. A total of 35 ODGJ caregivers became participants through the snowball sampling technique. The measurement uses a resilience scale and a happiness scale. The study's results showed a significant positive relationship between resilience and happiness in caregivers of ODGJ (r = 0.499 and sig. = 0.001). This indicates that resilience is one of the factors related to the increased happiness experienced by ODGJ caregivers in carrying out their duties and responsibilities.